Volatility spillover and co-movement among Chinese shipping sector stock index, oil futures price, ocean freight charge and exchange rate - Zitong Zhao (2020)
© 2019 IOP Publishing Ltd. All rights reserved. This study aims to analyze the co-movement and volatility spillover among four stock markets consist of Chinese shipping sector stock index, oil futures, shipping freight and currency market. We estimate dependence among these four markets using the multivariate copula model. Then we use the VAR model and impulse response function to investigate the volatility spillover among them. The empirical results show that the Gaussian copula is the most appropriate dependence mode as the AIC and BIC of this copula are the lowest when compared to other candidate copula models. The dependence correlation coefficients show a weak volatility dependence among these four markets. In addition, the results of the VAR suggest a spillover effect from shipping stock and oil to freight market.